A review of instruments measuring special educators' competencies. (18th May 2020) - Lee, Suk‐Hyang; Kim, Yu‐Ri; Park, Jiyeon
Abstract : The purpose of this study is to present a review of instruments developed to measure perceptions of special educators regarding their competencies and to provide a synthesis of research studies using these measurement instruments. A total of 29 studies were included in this review, and 20 instruments were used across the studies. The results were as follows. First, the majority of the instruments in this review were designed for assessing in‐service special educators. Second, there was a shortage of instruments designed for measuring necessary competencies in family supports and collaboration with families. Third, reliability and validity were reported for only 11 of the instruments. Finally, most studies utilised the tools in surveys; only two studies used the tools to investigate the effectiveness of the teacher support programmes implemented in their experiments. These results are discussed, and implications for future studies are proposed.